A study of pattern of adverse drug reactions in inpatients department of medicine of tertiary care hospital in Madhya Pradesh, India - Phadnis, Pradeep; Marko, Shashi (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Adverse Drug Reactions are the recognized hazards of drug therapy and they can occur with any class of drugs. The main aim of the study was to detect and analyze Adverse Drug Reactions in inpatients of medicine department in tertiarycare hospital. The study assesses the incidence and pattern of ADRs, identifying co-morbidities, past and present illness, assess causality and the offending drugs, monitoring and documenting suspected adverse drug reactions. Methods: A prospective study was conducted over a period of 6 months. The WHO definition of an ADR was adopted. Each ADR was assessed for its causality by using WHO probability scale. The severity of each ADR was assessed by using modified Hartwig et al, and Siegel scale. Results: A total 58 ADR were reported during study period out of which 28 (48.27%) were male and 30 (51.72%) were female patients. The assessment by WHO probability scale showed that out of 58 ADR 22 (37.93%) were probable and 17 (29.31%) were possible and 6 (10.34%) were certain. Most commonly involved system was gastrointestinal system with 24 (41.37%) ADRs. Severity assessment by modified Hartwig and Siegel scale showed that 22 (37.93%) were moderate, 32 (55.17%) were mild and 4 (6.89%) were severe ADRs. No lethal effects were observed or produced. Conclusions: The study concluded that Adverse Drug Reactions are common and some of them resulted in increased health care cost due to need of some interventions and increased length of hospital stay. The health system should promote the reporting of Adverse Drug Reactions, proper documentation and periodic reporting to regional pharmacovigilance centers to ensure drug safety.